معيار إثبات المقومات المعنوية للجريمة - عبد الله فراس عبد المنعم (Journal of Legal Sciences, 2017)
The legal structure of the crime, in addition to the material aspect, requires a personal aspect that the conduct of the offender is a result of a conscious free will that is capable of discrimination and choice and carries with it the wrong conduct that justifies the imposition of legal blame. The most important feature of the criminal law in the face of other branches of law is that it is more than attention to persons who speak to the law. It aims at justice, social rehabilitation and special and public deterrence, which must be directed to the offender before the crime or to the offender prior to the act. The criminal responsibility of self-determination distinguishes it from other forms of responsibility determined by other legal branches. It does not automatically follow the effect of the material violation of the rule of conduct contained in the criminalization text, but also requires a reflection of the criminal offenses in the same offender, To blame him, where his imam was a reasonable opportunity to avoid violating the rule of conduct, but nevertheless contrary to either deliberately, starting out a clear hostility to the social value of criminal protection, or unintentionally but in a way that reveals his disregard for the value of protection and shows that not to take more Be cautious and cautious of what I did, even though he could have done it. What is the criterion that can be relied upon to establish the existence of this personal or moral aspect of the accused? Is it a subjective criterion to examine the availability of a psychic course that is realistic and not presumptive and determines the scope of its responsibility according to its actual density, or is an objective criterion merely assumed, The spin-off that may result from doing it and in searching for the answer to this question and what relates to it is determined by the scope of the research.